A high-hardness and brittle semiconductor anti-deterioration cutting fluid and its production process

By adding anti-wear modifiers and lubricating antibacterial additives to the cutting fluid, the toxicity, pollution and insufficient performance of existing cutting oils was solved, and a high-hard and brittle semiconductor anti-deterioration cutting fluid was prepared, which had excellent lubricating, anti-wear, anti-bacterial and anti-rust properties.

CN119081755BActive Publication Date: 2025-04-18OEMETA (WUHAN) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411186194.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-04-18
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

The existing cutting oils used for semiconductor processing have problems of toxicity, irritation and environmental pollution, and their lubricating and anti-wear properties are insufficient, and they are prone to deterioration.

Method used

By adding anti-wear modifiers and lubricating antibacterial additives, a high-hard and brittle semiconductor anti-deterioration cutting fluid consists of lubricant, anti-wear modifier, organic acids, organic amines, lubricating antibacterial additives, bactericides, wetting agents, defoaming agents and deionized water. The anti-wear modifier is made by combining aminohexammonized boron nitride and silica nanoparticles, while the lubricated antibacterial additive is prepared by mixing aminohexammonized boron nitride and chitosan.

Benefits of technology

The cutting fluid has excellent lubricating wear resistance, antibacterial properties and anti-rust properties, which can effectively prevent deterioration and improve the performance and safety of semiconductor processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of cutting fluids, and discloses a high-hardness and brittle semiconductor anti-deterioration cutting fluid and a production process thereof. The cutting fluid comprises the following components by weight: 15 to 25 parts of lubricant, 10 to 20 parts of anti-wear modifier, 1 to 5 parts of organic acid, 5 to 15 parts of organic amine, 1 to 3 parts of lubricating antibacterial additive, 0.1 to 0.3 parts of bactericide, 0.5 to 2 parts of wetting agent, 0.1 to 0.5 parts of defoaming agent, and 25 to 35 parts of deionized water; the anti-wear modifier is prepared by using amino sodium The invention discloses a novel nanometer hexagonal boron nitride (HBN) nanoparticles, which are in situ grown on a carrier and hybridized with a dibasic acid ionic liquid. The dibasic acid ionic liquid is made of 2-(1,3-benzothiazole-2-thio)succinic acid and choline hydroxide. The lubricating and antibacterial additive is made of amino-modified nanometer hexagonal boron nitride, chitosan and ethylene glycol diglycidyl ether. The invention provides the cutting fluid with excellent lubricating and wear resistance, antibacterial property and rust prevention property by adding an anti-wear modifier and a lubricating and antibacterial additive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cutting fluids, and in particular relates to a high-hardness and brittle semiconductor anti-deterioration cutting fluid and a production process thereof. Background Art

[0002] At present, the lubricating and cooling fluid used in semiconductor processing in the hard and brittle material industry is mainly cutting oil. Cutting oil is a processing aid that plays the role of lubrication, cooling, cleaning and rust prevention in the material cutting process. With the rapid development of the manufacturing industry, the use of cutting oil has increased year by year. At present, industrial cutting oil is mostly mineral oil as the main component, and extreme pressure additives are added. It has certain toxicity and irritation. It will endanger the health of operators in long-term use. Subsequent processing and recycling will also cause environmental pollution and the generation of smoke cannot be controlled, resulting in reduced visibility in the workshop and worrying air quality. Especially for the processing of hard and brittle materials, the processing chips are small, and traditional cutting oil is easy to wrap the chips, making them adhere to the surface of the workpiece and difficult to clean. The working fluid is easy to grow bacteria and stink, and there is a hidden danger of burning when a large amount of cutting oil is recycled.

[0003] In comparison, water-based additives have the advantages of low cost, fire resistance, good thermal conductivity, and environmental protection. However, water can cause serious corrosion on metal surfaces. At the same time, the low viscosity of water makes it difficult to form an elastic fluid dynamic lubrication film between friction pairs, increasing the wear rate of friction pairs. The existing technology adds two-dimensional materials such as hexagonal boron nitride with excellent lubrication, thermal conductivity, and mechanical properties as water-based cutting fluid lubrication media. However, hexagonal boron nitride nanosheets are chemically inert and have high surface energy. They have poor dispersibility in the lubrication medium and are prone to agglomeration during sliding, which reduces their lubrication performance. At the same time, the different electronegativity of boron atoms and nitrogen atoms produces extremely strong polarity between the layers of hexagonal boron nitride, which can inhibit interlayer slippage, reducing the friction reduction and anti-wear performance of hexagonal boron nitride as a lubricating additive.

[0004] In addition, the use environment of cutting fluid is generally an open system, which is always facing erosion or attack from microorganisms in the environment. Microorganisms can enter the cutting fluid through media such as mixing water and air. Microorganisms may also grow due to factors such as operators, machine tools and workshop hygiene conditions, causing the cutting fluid to deteriorate easily and corrode the product. Summary of the invention

[0005] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a high-hardness and brittle semiconductor anti-deterioration cutting fluid and its production process, by adding anti-wear modifiers and lubricating antibacterial additives, the cutting fluid is endowed with excellent lubrication, wear resistance, antibacterial and rust prevention properties.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A high-hardness and brittle semiconductor anti-deterioration cutting fluid, composed of the following components in parts by weight: 15-25 parts of lubricant, 10-20 parts of anti-wear modifier, 1-5 parts of organic acid, 5-15 parts of organic amine, 1-3 parts of lubricating antibacterial additive, 0.1-0.3 parts of bactericide, 0.5-2 parts of wetting agent, 0.1-0.5 parts of defoaming agent, and 25-35 parts of deionized water;

[0008] The anti-wear modifier is prepared by hybridizing an anti-wear composite material and a dibasic acid ionic liquid, wherein the anti-wear composite material is prepared by in-situ growing silicon dioxide nanoparticles using amino-treated nano hexagonal boron nitride as a carrier, and the dibasic acid ionic liquid is prepared by reacting 2-(1,3-benzothiazole-2-thio)succinic acid and choline hydroxide; the lubricating antibacterial additive is prepared by mixing amino-treated nano hexagonal boron nitride and chitosan, and using ethylene glycol diglycidyl ether as a cross-linking agent.

[0009] Preferably, the preparation method of the anti-wear modifier comprises the following steps:

[0010] A. Ultrasonic dispersion of amino-modified nano hexagonal boron nitride in a citric acid solution to obtain a dispersion, sodium silicate was added to deionized water and mixed, ethanol was added dropwise under stirring, the temperature was raised to 75-85° C., the dispersion was added, and then a dilute sulfuric acid solution was added to adjust the pH value of the system to 5-6, and ethanol was added continuously. The reaction was stopped when the reaction temperature was maintained at 75-85° C. After the reaction was completed, the mixture was aged for 1-2 hours, and then centrifuged, washed, and dried to prepare an anti-wear composite material;

[0011] B. Take 2-(1,3-benzothiazole-2-thio)succinic acid and put it into a reactor filled with ethanol, add choline hydroxide and deionized water, stir and react for 10-12 hours, and after the reaction is completed, perform rotary evaporation and drying to prepare a dibasic acid ionic liquid;

[0012] C. The anti-wear composite material and the dibasic acid ionic liquid are dissolved in anhydrous ethanol, stirred evenly at a speed of 1100-1300 rpm for 0.5-1 h, and then ultrasonically dispersed for 2-3 h and dried in a vacuum drying oven to prepare an anti-wear modifier.

[0013] Preferably, in step B, the molar ratio of 2-(1,3-benzothiazole-2-thio)succinic acid to choline hydroxide is 1:2-2.5.

[0014] Preferably, in step C, the mass ratio of the anti-wear composite material to the dibasic acid ionic liquid is 3-7:1.

[0015] Preferably, the method for preparing the lubricating antibacterial additive comprises the following steps: dissolving chitosan in an acetic acid solution to obtain a chitosan solution, ultrasonically dispersing amino-modified nano-hexagonal boron nitride in deionized water to obtain a suspension, uniformly mixing the chitosan solution and the suspension, adding ethylene glycol diglycidyl ether, stirring and mixing for 6 to 7 hours, and preparing the lubricating antibacterial additive.

[0016] Preferably, the preparation method of the amino-modified nano hexagonal boron nitride comprises the following steps: taking nano hexagonal boron nitride into a reactor, adding sodium hydroxide solution and stirring for 42 to 48 hours, centrifuging, washing and drying, dissolving the obtained hydroxylated nano hexagonal boron nitride in a mixed solution of deionized water and ethanol, ultrasonically dispersing it uniformly, then adding 3-aminopropyltriethoxysilane, reacting at 55 to 70° C. for 7 to 8 hours, and after the reaction is completed, centrifuging, washing and drying to prepare the amino-modified nano hexagonal boron nitride.

[0017] Preferably, the lubricant is polyethylene glycol; the organic acid is one or more combinations of dodecanedioic acid, isononanoic acid, octanoic acid, neodecanoic acid, sebacic acid, and isooctanoic acid; the organic amine is one or more combinations of monoethanolamine, diethanolamine, triethanolamine, and isopropanolamine.

[0018] Preferably, the fungicide is one or more combinations of A, A', A"-trimethyl-1,3,5-triazine-1,3,5(2H,4H,6H)-triethanol, 1,2-benzisothiazolin-3-one, and 2-butyl-1,2-benzisothiazolin-3-one.

[0019] Preferably, the wetting agent is one of polyethylene glycol octylphenyl ether or sodium diisooctyl sulfosuccinate; and the defoaming agent is a water-soluble silicone defoaming agent.

[0020] Preferably, the production process of the high-hardness and brittle semiconductor anti-deterioration cutting fluid comprises the following steps: weighing each component by weight, adding lubricant to deionized water and stirring evenly, heating in a water bath to 40-60°C, adding anti-wear modifier, lubricating antibacterial additive, organic acid, organic amine, bactericide, wetting agent and defoaming agent in sequence under stirring conditions and continuing to stir evenly to prepare a high-hardness and brittle semiconductor anti-deterioration cutting fluid.

[0021] Beneficial effects of the present invention:

[0022] The invention firstly performs hydroxylation treatment on nano hexagonal boron nitride, and then uses 3-aminopropyltriethoxysilane to react with hydroxylated nano hexagonal boron nitride to prepare amino nano hexagonal boron nitride. The invention in-situ grows silicon dioxide nanoparticles on the surface of amino nano hexagonal boron nitride to prepare an anti-wear composite material. After silicon dioxide is loaded on the surface of nano hexagonal boron nitride, the nano hexagonal boron nitride modified by 3-aminopropyltriethoxysilane has a strong affinity to SiO3. 2- The confinement effect of ions inhibits the growth of silicon dioxide nanoparticles and inhibits the agglomeration of silicon dioxide nanoparticles. Nano hexagonal boron nitride can be used as an anti-wear lubricant, and silicon dioxide nanoparticles can be used as a friction reducer. The two act synergistically to give the cutting fluid excellent friction reduction and anti-wear properties. In addition, the present invention utilizes 2-(1,3-benzothiazole-2-sulfenyl)succinic acid and choline hydroxide to react to synthesize a dibasic acid ionic liquid with good water solubility, and then hybridizes the dibasic acid ionic liquid with the anti-wear composite material through π-π interaction to prepare an anti-wear modifier. The presence of the dibasic acid ionic liquid can effectively improve the interfacial adsorption performance of the anti-wear composite material, so that the anti-wear composite material can be closely attached to the friction surface to form a protective film to continuously play a role, and the presence of the anti-wear composite material protective film can block more dibasic acid ionic liquids from being adsorbed on the contact interface, effectively avoiding the local aggregation of the dibasic acid ionic liquid, and achieving the effect of preventing the dibasic acid ionic liquid from corroding the contact interface. In addition, the present invention mixes amino nano hexagonal boron nitride and chitosan, and uses ethylene glycol diglycidyl ether as a cross-linking agent to prepare a lubricating antibacterial additive. The epoxy group in the structure of ethylene glycol diglycidyl ether reacts chemically with the amino group in the structure of amino nano hexagonal boron nitride and chitosan to form a cross-linked network structure, which gives the cutting fluid excellent lubrication and antibacterial effects. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1 A method for preparing amino-modified nano hexagonal boron nitride comprises the following steps:

[0025] Take 2g of nano hexagonal boron nitride in a reactor, add a sodium hydroxide solution with a mass concentration of 40% and stir for 42h. After centrifugation, washing and drying, the obtained hydroxylated nano hexagonal boron nitride is dissolved in a mixed solution of 120mL deionized water and 240mL ethanol, ultrasonically dispersed evenly, and then 5g of 3-aminopropyltriethoxysilane is added and reacted at 65°C for 8h. After the reaction is completed, it is centrifuged, washed and dried to prepare amino nano hexagonal boron nitride.

[0026] Example 2 A method for preparing an anti-wear modifier comprises the following steps:

[0027] A. The amino-modified nano hexagonal boron nitride prepared in Example 1 was ultrasonically dispersed in a 1.8 mol / L citric acid solution to obtain a dispersion, 400 g of sodium silicate was added to 1200 mL of deionized water and mixed, 12.5 mL of ethanol was added dropwise under stirring, the temperature was raised to 80° C., the obtained dispersion was added, and then a dilute sulfuric acid solution was added to adjust the pH value of the system to 6, and 800 mL of ethanol was added continuously. The reaction was stopped when the reaction temperature was maintained at 80° C. After the reaction was completed, the mixture was aged for 2 h, and then centrifuged, washed, and dried to obtain an anti-wear composite material;

[0028] B. Take 5.6g of 2-(1,3-benzothiazole-2-thio)succinic acid and put it into a reactor filled with 50mL of ethanol, add 5g of choline hydroxide and 12mL of deionized water, stir and react for 12h, and after the reaction is completed, perform rotary evaporation and drying to prepare a dibasic acid ionic liquid;

[0029] C. Take 6.7 g of the anti-wear composite material and 2 g of the dibasic acid ionic liquid and dissolve them in 50 mL of anhydrous ethanol, stir them evenly at a speed of 1200 rpm for 1 hour, then ultrasonically disperse them for 3 hours and dry them in a vacuum drying oven to prepare an anti-wear modifier.

[0030] Example 3 A method for preparing a lubricating antibacterial additive comprises the following steps:

[0031] 1.6 g of chitosan was dissolved in 50 mL of 2% acetic acid solution to obtain a chitosan solution. 0.3 g of the amino-modified nano-hexagonal boron nitride prepared in Example 1 was ultrasonically dispersed in 5 mL of deionized water to obtain a suspension. The chitosan solution and the suspension were evenly mixed. 0.5 g of ethylene glycol diglycidyl ether was added and stirred for 7 hours to prepare a lubricating antibacterial additive.

[0032] Example 4 A high-hardness and brittle semiconductor anti-deterioration cutting fluid is composed of the following components in parts by weight: 15 parts of polyethylene glycol, 10 parts of the anti-wear modifier prepared in Example 2, 2 parts of sebacic acid, 5 parts of triethanolamine, 1 part of the lubricating and antibacterial additive prepared in Example 3, 0.1 part of 1,2-benzisothiazolin-3-one, 0.5 part of sodium diisooctyl sulfosuccinate, 0.1 part of water-soluble silicone defoaming agent, and 25 parts of deionized water.

[0033] The production process of the above-mentioned high hardness and brittle semiconductor anti-deterioration cutting fluid comprises the following steps:

[0034] Weigh each component by weight, add lubricant to deionized water and stir evenly, heat to 45°C in a water bath, add anti-wear modifier, lubricating antibacterial additive, organic acid, organic amine, bactericide, wetting agent and defoaming agent in sequence under stirring and continue to stir evenly to prepare a high-hardness and brittle semiconductor anti-deterioration cutting fluid.

[0035] Example 5 A high-hardness, brittle semiconductor anti-deterioration cutting fluid is composed of the following components in parts by weight: 20 parts of polyethylene glycol, 15 parts of the anti-wear modifier prepared in Example 2, 3 parts of sebacic acid, 7 parts of triethanolamine, 2 parts of the lubricating and antibacterial additive prepared in Example 3, 0.2 parts of 1,2-benzisothiazolin-3-one, 1 part of sodium diisooctyl sulfosuccinate, 0.3 parts of water-soluble silicone defoaming agent, and 30 parts of deionized water.

[0036] The production process of the above-mentioned high-hardness and brittle semiconductor anti-deterioration cutting fluid is the same as that of Example 4.

[0037] Example 6 A high-hardness, brittle semiconductor anti-deterioration cutting fluid is composed of the following components in parts by weight: 25 parts of polyethylene glycol, 20 parts of the anti-wear modifier prepared in Example 2, 5 parts of sebacic acid, 12 parts of triethanolamine, 3 parts of the lubricating and antibacterial additive prepared in Example 3, 0.3 parts of 1,2-benzisothiazolin-3-one, 1.5 parts of sodium diisooctyl sulfosuccinate, 0.5 parts of water-soluble silicone defoaming agent, and 34 parts of deionized water.

[0038] The production process of the above-mentioned high-hardness and brittle semiconductor anti-deterioration cutting fluid is the same as that of Example 4.

[0039] Comparative Example 1 A method for preparing an anti-wear modifier comprises the following steps:

[0040] A. Take 5.6g of 2-(1,3-benzothiazole-2-thio)succinic acid and put it into a reactor filled with 50mL of ethanol, add 5g of choline hydroxide and 12mL of deionized water, stir and react for 12h, and after the reaction is completed, perform rotary evaporation and drying to prepare a dibasic acid ionic liquid;

[0041] B. Take 6.7 g of nano hexagonal boron nitride and 2 g of dibasic acid ionic liquid and dissolve them in 50 mL of anhydrous ethanol. Stir them evenly at a speed of 1200 rpm for 1 hour, then ultrasonically disperse them for 3 hours and dry them in a vacuum drying oven to prepare an anti-wear modifier.

[0042] Comparative Example 2 A method for preparing an anti-wear modifier comprises the following steps:

[0043] The amino-modified nano hexagonal boron nitride prepared in Example 1 was ultrasonically dispersed in a 1.8 mol / L citric acid solution to obtain a dispersion. 400 g of sodium silicate was added to 1200 mL of deionized water and mixed. 12.5 mL of ethanol was added dropwise under stirring. The temperature was raised to 80° C., the obtained dispersion was added, and then a dilute sulfuric acid solution was added to adjust the pH value of the system to 6. 800 mL of ethanol was continued to be added. The reaction was stopped when the reaction temperature was maintained at 80° C. After the reaction was completed, it was aged for 2 h, and then centrifuged, washed, and dried to prepare an anti-wear modifier.

[0044] Comparative Example 3 A high-hardness and brittle semiconductor anti-deterioration cutting fluid is composed of the following components in parts by weight: 25 parts of polyethylene glycol, 20 parts of the anti-wear modifier prepared in Comparative Example 1, 5 parts of sebacic acid, 12 parts of triethanolamine, 3 parts of the lubricating and antibacterial additive prepared in Example 3, 0.3 parts of 1,2-benzisothiazolin-3-one, 1.5 parts of sodium diisooctyl sulfosuccinate, 0.5 parts of water-soluble silicone defoaming agent, and 34 parts of deionized water.

[0045] The production process of the above-mentioned high-hardness and brittle semiconductor anti-deterioration cutting fluid is the same as that of Example 4.

[0046] Comparative Example 4 A high-hardness and brittle semiconductor anti-deterioration cutting fluid is composed of the following components in parts by weight: 25 parts of polyethylene glycol, 20 parts of the anti-wear modifier prepared in Comparative Example 2, 5 parts of sebacic acid, 12 parts of triethanolamine, 3 parts of the lubricating and antibacterial additive prepared in Example 3, 0.3 parts of 1,2-benzisothiazolin-3-one, 1.5 parts of sodium diisooctyl sulfosuccinate, 0.5 parts of water-soluble silicone defoaming agent, and 34 parts of deionized water.

[0047] The production process of the above-mentioned high-hardness and brittle semiconductor anti-deterioration cutting fluid is the same as that of Example 4.

[0048] Comparative Example 5 A high-hardness and brittle semiconductor anti-deterioration cutting fluid is composed of the following components in parts by weight: 25 parts of polyethylene glycol, 20 parts of the anti-wear modifier prepared in Example 2, 5 parts of sebacic acid, 12 parts of triethanolamine, 0.3 parts of 1,2-benzisothiazolin-3-one, 1.5 parts of sodium diisooctyl sulfosuccinate, 0.5 parts of water-soluble silicone defoaming agent, and 34 parts of deionized water.

[0049] The production process of the above-mentioned high-hardness and brittle semiconductor anti-deterioration cutting fluid is the same as that of Example 4.

[0050] Performance Testing

[0051] The cutting fluids prepared in Examples 4-6 and Comparative Examples 3-5 were subjected to performance testing:

[0052] (1) Antibacterial performance test: The antibacterial performance test was carried out according to ASTM D3946-92 standard. First, 900 mL of the cutting fluid prepared in Examples 4-6 and Comparative Examples 3-5 was added to a beaker, and then 100 mL of the cultured bacteria and nutrients required by microorganisms such as iron filings, corn starch, and casein were added and stirred evenly. The beaker was placed in a 30°C constant temperature water bath, and air was ventilated into the sample. The cycle was 7 days, and each cycle was ventilated for 5 days and stopped for 2 days. During this process, sterile water was added to make up for the loss caused by evaporation, and the total number of bacterial and fungal colonies in the sample was regularly tested. The sample deterioration index is: total bacterial count>10 7 cfu / mL, total fungal count>10 2 cfu / mL, and recorded the time required for the sample to deteriorate. The data results are shown in Table 1.

[0053] (2) Wear resistance test: tested in accordance with GB / T 3142-2019; Anti-corrosion and anti-rust performance test: tested in accordance with GB / T6144-2010 standard, and the data results are shown in Table 1.

[0054] Table 1 Test results of sample performance

[0055]

[0056] As can be seen from the data in Table 1, the cutting fluids prepared in Examples 4-6 of the present invention have excellent lubrication, wear resistance, antibacterial and rust-proof properties. The anti-wear modifier added in Comparative Example 3 is prepared by mixing only nano hexagonal boron nitride and dibasic acid ionic liquid, and the anti-wear modifier added in Comparative Example 4 does not contain dibasic acid ionic liquid components. The maximum non-seizure load measured in Comparative Examples 3-4 is lower than that in Examples 4-6, and the corrosion time is reduced compared with that in Example 4-6, indicating that the in-situ growth of silicon dioxide nanoparticles on the surface of amino-treated nano hexagonal boron nitride and the addition of dibasic acid ionic liquid can give the cutting fluid excellent anti-wear and rust-proof properties. No lubrication and antibacterial additives are added in Comparative Example 5, and the measured deterioration time is significantly reduced compared with Examples 4-6.

[0057] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0058] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A high hardness and brittle semiconductor anti-deterioration cutting fluid, characterized in that: The invention is composed of the following components in parts by weight: 15-25 parts of lubricant, 10-20 parts of anti-wear modifier, 1-5 parts of organic acid, 5-15 parts of organic amine, 1-3 parts of lubricating antibacterial additive, 0.1-0.3 parts of bactericide, 0.5-2 parts of wetting agent, 0.1-0.5 parts of defoaming agent and 25-35 parts of deionized water; The anti-wear modifier is made by hybridizing an anti-wear composite material and a dibasic acid ionic liquid, wherein the anti-wear composite material is made by in-situ growing silicon dioxide nanoparticles using amino-treated nano hexagonal boron nitride as a carrier, and the dibasic acid ionic liquid is made by reacting 2-(1,3-benzothiazole-2-thio)succinic acid and choline hydroxide; the lubricating antibacterial additive is made by mixing amino-treated nano hexagonal boron nitride and chitosan, and using ethylene glycol diglycidyl ether as a cross-linking agent; The preparation method of the anti-wear modifier comprises the following steps: A. Ultrasonic dispersion of amino-modified nano hexagonal boron nitride in a citric acid solution to obtain a dispersion, sodium silicate was added to deionized water and mixed, ethanol was added dropwise under stirring, the temperature was raised to 75-85° C., the dispersion was added, and then a dilute sulfuric acid solution was added to adjust the pH value of the system to 5-6, and ethanol was added continuously. The reaction was stopped when the reaction temperature was maintained at 75-85° C. After the reaction was completed, the mixture was aged for 1-2 hours, and then centrifuged, washed, and dried to prepare an anti-wear composite material; B. Take 2-(1,3-benzothiazole-2-thio)succinic acid and put it into a reactor filled with ethanol, add choline hydroxide and deionized water, stir and react for 10-12 hours, and after the reaction is completed, perform rotary evaporation and drying to prepare a dibasic acid ionic liquid; C. Dissolve the anti-wear composite material and the dibasic acid ionic liquid in anhydrous ethanol, stir evenly at a speed of 1100-1300 rpm for 0.5-1 h, and then ultrasonically disperse for 2-3 h and dry in a vacuum drying oven to prepare an anti-wear modifier; The preparation method of the lubricating antibacterial additive comprises the following steps: dissolving chitosan in an acetic acid solution to obtain a chitosan solution, ultrasonically dispersing amino-modified nano hexagonal boron nitride in deionized water to obtain a suspension, uniformly mixing the chitosan solution and the suspension, adding ethylene glycol diglycidyl ether, stirring and mixing for 6-7 hours, and preparing the lubricating antibacterial additive.

2. The high hardness and brittle semiconductor anti-deterioration cutting fluid according to claim 1 is characterized in that: In the step B, the molar ratio of 2-(1,3-benzothiazole-2-thio)succinic acid to choline hydroxide is 1:2-2.

5.

3. The high hardness and brittle semiconductor anti-deterioration cutting fluid according to claim 1 is characterized in that: In step C, the mass ratio of the anti-wear composite material to the dibasic acid ionic liquid is 3-7:

1.

4. The high hardness and brittle semiconductor anti-deterioration cutting fluid according to claim 1, characterized in that: The preparation method of the amino-modified nano hexagonal boron nitride comprises the following steps: taking nano hexagonal boron nitride into a reactor, adding sodium hydroxide solution and stirring for 42-48 hours, centrifuging, washing and drying, dissolving the obtained hydroxylated nano hexagonal boron nitride in a mixed solution of deionized water and ethanol, uniformly dispersing by ultrasonication, then adding 3-aminopropyltriethoxysilane, reacting at 55-70°C for 7-8 hours, and centrifuging, washing and drying after the reaction is completed to prepare the amino-modified nano hexagonal boron nitride.

5. The high hardness and brittle semiconductor anti-deterioration cutting fluid according to claim 1, characterized in that: The lubricant is polyethylene glycol; the organic acid is one or more combinations of dodecanedioic acid, isononanoic acid, octanoic acid, neodecanoic acid, sebacic acid, and isooctanoic acid; the organic amine is one or more combinations of monoethanolamine, diethanolamine, triethanolamine, and isopropanolamine.

6. The high hardness and brittle semiconductor anti-deterioration cutting fluid according to claim 1, characterized in that: The fungicide is one or more combinations of A, A', A"-trimethyl-1,3,5-triazine-1,3,5(2H,4H,6H)-triethanol, 1,2-benzisothiazolin-3-one, and 2-butyl-1,2-benzisothiazolin-3-one.

7. The high hardness and brittle semiconductor anti-deterioration cutting fluid according to claim 1, characterized in that: The wetting agent is one of polyethylene glycol octyl phenyl ether or sodium diisooctyl sulfosuccinate; and the defoaming agent is a water-soluble organic silicon defoaming agent.

8. The high hardness and brittle semiconductor anti-deterioration cutting fluid according to claim 1, characterized in that: Production process of highly hard and brittle semiconductor anti-deterioration cutting fluid The method comprises the following steps: weighing each component by weight, adding a lubricant to deionized water and stirring evenly, heating the mixture to 40-60° C. in a water bath, sequentially adding an anti-wear modifier, a lubricating antibacterial additive, an organic acid, an organic amine, a bactericide, a wetting agent and a defoaming agent under stirring conditions, and continuing to stir evenly to prepare a high-hardness and brittle semiconductor anti-deterioration cutting fluid.

Citation Information

Patent Citations

  • Preparation method of spherical nano silica-coated hexagonal boron nitride composite powder

    CN104974817A

  • Anti-wear hydraulic oil with low friction coefficient

    CN114854474A

  • Antibacterial hydrogel with rapid cooling and thermochromic effects and preparation method thereof

    CN116948218A

  • Cutting fluid for hard and brittle materials and preparation method thereof

    CN116970430A